A Key Role for NF-κB Transcription Factor c-Rel in T-Lymphocyte-Differentiation and Effector Functions. (6th March 2012) - Visekruna, Alexander; Volkov, Anton; Steinhoff, Ulrich
Abstract : The transcription factors of the Rel/NF- κ B family function as key regulators of innate and adoptive immunity. Tightly and temporally controlled activation of NF- κ B-signalling pathways ensures prevention of harmful immune cell dysregulation, whereas a loss of control leads to pathological conditions such as severe inflammation, autoimmune disease, and inflammation-associated oncogenesis. Five family members have been identified in mammals: RelA (p65), c-Rel, RelB, and the precursor proteins NF- κ B1 (p105) and NF- κ B2 (p100), that are processed into p50 and p52, respectively. While RelA-containing dimers are present in most cell types, c-Rel complexes are predominately found in cells of hematopoietic origin. In T-cell lymphocytes, certain genes essential for immune function such as Il2 and Foxp3 are directly regulated by c-Rel. Additionally, c-Rel-dependent IL-12 and IL-23 transcription by macrophages and dendritic cells is crucial for T-cell differentiation and effector functions. Accordingly, c-Rel expression in T cells and antigen-presenting cells (APCs) controls a delicate balance between tolerance and immunity. This review gives a selective overview on recent progress in understanding of diverse roles of c-Rel in regulating adaptive immunity.